Michaela Kidwell: capstone - Kidwell, Michaela, artist (Colorado State University. Libraries, 2026)
The artist's statement: There is a duality in my work that I strive to live in balance with. I revel in the gentle beauty of nature, but I am drawn to the raw and unconventional aspects of the human experience. I walk the line between these two subjects in my work. As a graphic designer, I seek to learn new perspectives and tell stories with authenticity and purpose. The main creative software I use is Adobe Illustrator, InDesign, Photoshop, and Procreate. My artistic process tends to be methodical and rooted in research. I begin with fully immersing myself with the subject at hand by collecting relevant information and references. I look to artists who push boundaries in design and passionately portray their messages. Those who lead with raw authenticity and actively question the status quo. I'm inspired by the perfect imperfection of natural landscapes, the inner peace one feels surrounded by nature, and the idea of creating a better future for the fragile world around us. In this piece, I created an illustration that would complement this flame typeface. The purpose of this poster was to spark commentary on the phone addiction crisis and the negative effects of doomscrolling. My goal was to capture an unflattering yet realistic depiction of where one might doomscroll.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design